PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PADA SISWA KELAS X MIPA SMA NEGERI 1 PONTIANAK - Amsal Amsal (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
This study is entitled "The Use of Problem Based Learning Models to Increase Physics Learning Outcomes in Class X MIPA Students of SMA Negeri 1 Pontianak". This research studies to study the process of activities and analyze each cycle in improving learning models using the Problem Based Learning (PBL) learning model. This research is a classroom action research conducted over two cycles with the help of teacher observation sheets and 36 student achievement test results, and each cycle consists of 2 meetings. Each cycle of the cycle consists of planning the action, implementing the action, observing the action, reflecting on the action. The data in this study are data analysis of the implementation of learning using Problem Based Learning learning models and data on student learning outcomes improvement. Data analysis of learning implementation using the Problem Based Learning model was obtained on the teacher observation sheet. Based on the results of the analysis of teacher activity data with a mastery level of learning models in the first cycle of 86.54% while for the second cycle of 94.23%, an increase in mastery of the learning model was 7.69%. While learning outcomes also increased from an average value of cycle I of 45.22 to an average value of cycle II of 62.08, meaning an increase of 16.86 from cycle I to cycle II. This shows that the Problem Based Learning model can improve student learning outcomes.